Legendary frybread drive-in : intertribal stories - Smith, Cynthia Leitich; Hart, Kate, 1980-; Gansworth, Eric, 1965-; Bell, Marcella; Little Badger, Darcie, 1987-; Adams, Kaua Mahoe; Boulley, Angeline; Cobell, K. A.; Eversole, A. J.; Ferguson, Jenny, 1985-; Graves, Byron; Hartman Derr, Christine; et al. (Heartdrum, 2025)
Set at a classic drive-in restaurant that seems to exist in every Native community, this anthology unites the stories of teens from all kinds of backgrounds through the shared theme of Native joy, with stories and poems reflecting hope, healing, humor, love, friendship, romance, and joy. The road to Sandy June's Legendary Frybread Drive-In slips through every rez and alongside every urban Native hangout. The menu offers a rotating feast, including traditional eats and tasty snacks. But Sandy June's serves up more than food: it hosts live music, movie nights, unexpected family reunions, love long lost, and love found again. That big green-and-gold neon sign beckons to teens of every tribal Nation, often when they need it most. Featuring the voices of both new and acclaimed Indigenous writers, and edited by bestselling Muscogee author Cynthia Leitich Smith, this collection of interconnected stories serves up laughter, love, Native pride, and the world's best frybread.